2010
DOI: 10.1111/j.1600-051x.2010.01601.x
|View full text |Cite
|
Sign up to set email alerts
|

Gingival overgrowth in subjects under immunosuppressive regimens based on cyclosporine, tacrolimus, or sirolimus

Abstract: Pharmacological and periodontal variables were associated with GO in different immunosuppressive regimens. Integration between the medical and the dental team may be an important approach in the post-transplant maintenance routine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 35 publications
3
42
0
4
Order By: Relevance
“…Animal research indicated a higher proportion of Pg in the test sites of CsA‐medicated beagle dogs . A recent study showed that GO subjects presented a higher frequency of Tf in the salivary samples of immunosuppressed patients under the administration of CsA, tacrolimus, or sirolimus . The results of the present study demonstrated a relationship between the prevalence of red complex and CsA‐induced GO.…”
Section: Discussionsupporting
confidence: 70%
“…Animal research indicated a higher proportion of Pg in the test sites of CsA‐medicated beagle dogs . A recent study showed that GO subjects presented a higher frequency of Tf in the salivary samples of immunosuppressed patients under the administration of CsA, tacrolimus, or sirolimus . The results of the present study demonstrated a relationship between the prevalence of red complex and CsA‐induced GO.…”
Section: Discussionsupporting
confidence: 70%
“…The drug categories and representative drugs including the newer drugs are listed in Table 1. [1][2][3][4][5] Ellis et al 6) discussed the overall prevalence of gingival overgrowth related to chronic medication with CCBs, addressing it is considerably lower than finding from previous studies. Therefore, the expression of this effect needs cofactors such as the presence of gingival inflammation or concomitant medications inducing gingival overgrowth.…”
Section: Introductionmentioning
confidence: 51%
“…It is believed that CsA affects the fibroblasts, increasing their proliferation, as well as other extracellular factors. This suggests a significant role of dental plaque, in which CsA can accumulate (13,23,24 ). So as previous publications had showed, it is possible to place dental implants in patients with long-term immunosuppressive therapy following organ transplants, but this subject needs further and more extensive research.…”
Section: Discussionmentioning
confidence: 99%